No Absolutism Here: Harm Predicts Moral Judgment 30× Better Than Disgust—Commentary on Scott, Inbar, & Rozin (2016). (May 2016) - Gray, Kurt; Schein, Chelsea
Moral absolutism is the idea that people's moral judgments are insensitive to considerations of harm. Scott, Inbar, and Rozin (2016, this issue) claim that most moral opponents to genetically modified organisms are absolutely opposed—motivated by disgust and not harm. Yet there is no evidence for moral absolutism in their data. Perceived risk/harm is the most significant predictor of moral judgments for "absolutists, " accounting for 30 times more variance than disgust. Reanalyses suggest that disgust is not even a significant predictor of the moral judgments of absolutists once accounting for perceived harm and anger. Instead of revealing actual moral absolutism, Scott et al. find only empty absolutism : hypothetical, forecasted, self-reported moral absolutism. Strikingly, the moral judgments of so-called absolutists are somewhat more sensitive to consequentialist concerns than those of nonabsolutists. Mediation reanalyses reveal that moral judgments are most proximally predicted by harm and not disgust, consistent with dyadic morality.